Engineered Exosomes-Mediated Transfer of hsa-miR-320a Overcomes Chemoresistance in Cervical Cancer Cells via Targeting MCL1 - Zhou, Jinling; Wang, Yuanhe; Zhang, Lizhu; Chen, Qin; Zhu, Xiaojun; Jiang, Peiyue; Jiang, Nan; Zhao, Wei; Li, Baohua (Frontiers in Pharmacology, 2022)
In cervical cancer (CC), cisplatin resistance greatly restricts the application in clinical. Here, we report that engineered exosomes-mediated transfer of hsa-miR-320a overcomes chemoresistance in cervical cancer cells via targeting Myeloid Cell Leukemia Sequence 1 (MCL1). In DDP resistant CC tissues, as well as cell lines, it was found that miR-320a expression is lower, engineered miR-320a exosomes were used to attenuate DDP resistance in Hela/DDP and Caski/DDP cells. Mechanistically, we find that MCL1, which is a target of miR-320a, overcomes DDP resistance in Hela/DDP cells and in mice. In conclusion, we report that the engineered miR-320a exosomes is proved to be effective and safe.